(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2020)
Aim: To understand the co-relation between the weight of spectacle and the contact area of nose pads with respect to standard alignment. Study Design: A cross-sectional study. Method: Parameters such as weight of spectacle, frontal angle of nose and nose pads, splay angle of nose and nose pads and pantoscopic angle, area of nose pads and contact area of nose pads were measured using simple tools such as portable weighing machine and a handmade gauge similar to Fairbanks facial gauge and the correlation between all the parameters was found out. Results: Out of total 75 frames, 42 frames (56%) had no change in contact area with the corre sponding area of nose pads with respect to the parameters including weight of spectacle frontal angle, splay angle and pantoscopic angle in standard alignment of spectacle, while other 33 frames (44%) had a noticeable change in the contact area of nose pads with respect to the cor responding parameters. Conclusion: Difference of 50mm2of area between contact area and area of nose pads is ac ceptable with current trend of frames. Current trend of light weight frames and lenses has giv en ease to alignment as even misalignment does not result into marks. Contact area corre sponding with the area of nose pad play a significant role in distribution of spectacle weight on nose. Mismatch between contact area and area of nose pads will result into skin marks.Ideally, a wearer is happy when standard alignment is achieved with respect to facial measurements.